2000
DOI: 10.1099/0022-1317-81-7-1839
|View full text |Cite
|
Sign up to set email alerts
|

Multiple infection, recombination and genome relationships among begomovirus isolates found in cotton and other plants in Pakistan

Abstract: Begomoviruses occur in many plant species in Pakistan and are associated with an epidemic of cotton leaf curl disease that has developed since 1985. PCR analysis with primer pairs specific for each of four already sequenced types of DNA-A of cotton leaf curl virus (CLCuV-PK types a, 26, 72b and 804a), or for okra yellow vein mosaic virus (OYVMV), indicated that many individual naturally infected plants of cotton and other malvaceous species contained two or three begomovirus sequences. Similarly, sequence diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
79
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(84 citation statements)
references
References 25 publications
5
79
0
Order By: Relevance
“…Geminiviruses are characterized by twin icosahedral capsids and small, single-stranded DNA (ssDNA) genomes (56) that display high levels of genetic variability (62). Several studies have indicated that recombination contributes to geminivirus diversity (48,60,71). However, unlike doublestranded DNA (dsDNA) viruses, there is also mounting evidence that ssDNA viruses are subject to high nucleotide mutation rates similar to the levels reported previously for RNA viruses (34,35,53).…”
mentioning
confidence: 89%
“…Geminiviruses are characterized by twin icosahedral capsids and small, single-stranded DNA (ssDNA) genomes (56) that display high levels of genetic variability (62). Several studies have indicated that recombination contributes to geminivirus diversity (48,60,71). However, unlike doublestranded DNA (dsDNA) viruses, there is also mounting evidence that ssDNA viruses are subject to high nucleotide mutation rates similar to the levels reported previously for RNA viruses (34,35,53).…”
mentioning
confidence: 89%
“…Numerous examples of recombination in geminiviruses have been reported, between members both belonging to the same genus (Hou & Gilbertson, 1996;Zhou et al, 1997;Navas-Castillo et al, 2000;Sanz et al, 2000;Martin et al, 2001;Monci et al, 2002, Ndunguru et al, 2005Bull et al, 2006;García-Andrés et al, 2006;Owor et al, 2007) and of different genera (Briddon et al, 1996;Klute et al, 1996). Recombination can result in significant changes in the biological properties of viruses, such as the ability to increase the relative fitness (Fernández-Cuartero et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…It appears to heavily contribute to begomovirus genetic diversity, increasing the evolutionary potential and local adaptation of strains (Berrie et al, 2001;Graham et al, 2010;Harrison & Robinson, 1999;Monci et al, 2002;Padidam et al, 1999). There is ample opportunity for recombination because multiple begomovirus species are often found co-infecting the same plant (Davino et al, 2009;García-Andrés et al, 2006;Harrison et al, 1997;Pita et al, 2001;Ribeiro et al, 2003;Sanz et al, 2000;Torres-Pacheco et al, 1996), and more than one virus can simultaneously replicate in the same nucleus (Morilla et al, 2004). Additionally, the high recombination frequency observed for begomoviruses may be explained by a theoretical recombination-dependent replication mechanism (RDR) (Jeske et al, 2001), in addition to the welldocumented rolling circle replication (RCR) (Saunders et al, 2001).…”
Section: Introductionmentioning
confidence: 99%